Dispositional Mindfulness May Have Protected Athletes from Psychological Distress During COVID-19 in Australia. Issue 3 (June 2022) - O'Connor, Edward J.; Crozier, Alyson J; Murphy, Alistair; Immink, Maarten A
Promoting athlete wellbeing has become a priority in elite sport, and the COVID-19 pandemic has accentuated the need for a comprehensive understanding of risk and protective factors. Existing sport research has not yet considered whether specific cognitive factors such as dispositional mindfulness and executive function may protect athletes against psychological distress. In a sample of high-performance Australian football athletes ( n = 27), we administered measures of dispositional mindfulness (MAAS), executive function (AOSPAN; eStroop), and psychological distress (APSQ) at pre-season, coinciding with the initial (2020) COVID-19-related sport shutdown in Australia. Measures of executive function and psychological distress were re-administered at the end of the COVID-19 affected competitive season in 2020. Athletes reported significantly elevated psychological distress relative to previous estimates of distress among high-performance athletes established in prior studies. Executive functions, including working memory and inhibitory control were not significantly associated with psychological distress or dispositional mindfulness at either timepoint. However, baseline mindfulness was associated with reduced distress at both pre-season (r = −0.48, p = .03) and end of season (r = −0.56, p = .004), suggesting that dispositional mindfulness may have afforded protective buffering against symptoms of distress. Correlation data alone does not establish a directional connection from mindfulness to reduced distress, and future research is required to elucidate this association and/or establish the mechanism/s by which dispositional mindfulness may protect against psychological distress in this population.